2005
DOI: 10.1016/j.femsim.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunisation with novelStreptococcus pneumoniaeprotein antigens enhances bacterial clearance in an acute mouse lung infection model

Abstract: Streptococcus pneumoniae contains many proteins that have not been evaluated as potential protective vaccine antigens. In this study we isolated proteins from a serotype 3 strain of S. pneumoniae for use in mouse immunisation studies. Separation of the protein mix was achieved by SDS-PAGE electrophoresis followed by electro-elution to isolate individual proteins. This procedure successfully separated 21 fractions from which six proteins were selected based on purity and quantity and were initially denoted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It has also been reported that GADPH is an immunogenic protein found on the cell wall of SS [15]. GAPDH is reported in the development of subunit vaccines against Edwardsiella tarda [31], [32], Streptococcus pneumoniae [33] and Bacillus anthracis [34].…”
Section: Discussionmentioning
confidence: 96%
“…It has also been reported that GADPH is an immunogenic protein found on the cell wall of SS [15]. GAPDH is reported in the development of subunit vaccines against Edwardsiella tarda [31], [32], Streptococcus pneumoniae [33] and Bacillus anthracis [34].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we focused on testing the S. pneumoniae-derived RP-L7/L12 protein, which we argue is a more appropriate target for detecting S. pneumoniae in the following ways. First, RP-L7/L12 is a component of the 50S ribosome, which is abundant in all bacteria and is specific for each bacterial species (26,34). Second, the RP-L7/L12 levels increase in proportion to the bacterial growth rate, since the protein is essential for protein synthesis in bacteria (25,35).…”
Section: Discussionmentioning
confidence: 99%
“…This recruitment into the lung is in response to bacterial lipopolysacharide and a range of inflammatory mediators that are released by resident phagocytes and endothelial cells of the bronchus (Dunkley et al, 1995). Immunization with antigens from NTHi, Streptococcus pneumoniae and Pseudomonas aeruginosa have previously been reported to enhance the recruitment of white cells (both neutrophils and monocytes) when the lung is challenged with live microbes (Buret et al, 1994; Foxwell et al, 2001; Jomaa et al, 2005b). Furthermore, this recruitment is antigen dependent with immunization by WKCs normally be the most effective (Jomaa et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%